2020
DOI: 10.1101/2020.08.06.239897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient dominance governs the assembly of microbial communities in mixed nutrient environments

Abstract: A major open question in microbiome research is whether we can predict how the components of a diet collectively determine the taxonomic composition of microbial communities. Motivated by this challenge, here we ask whether communities assembled in a mixed nutrient environment can be predicted from those assembled in every single nutrient in isolation. To that end, we first formulate a quantitative null model of community assembly in a mixture of nutrients that recruit species independently. We then test the m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…Interestingly, in our petal community members of the Pseudomonadaceae and Enterobacteriaceae are common ( Figure A3), and recent studies have shown that these same two families tend to dominate communities assembled in minimal media with carbon as the main limiting resource (Goldford et al, 2018). In these artificial communities, as in our functional tests, Enterobacteriaceae tend to grow better on sugars, and Pseudomonadaceae in organic acids (Estrela et al, 2020). An extreme case of this potential specialization was the Rosenbergiella species, which are known nectar inhabitants.…”
Section: Functional Characterization Of Bacteria Of the Ray Petal Csupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, in our petal community members of the Pseudomonadaceae and Enterobacteriaceae are common ( Figure A3), and recent studies have shown that these same two families tend to dominate communities assembled in minimal media with carbon as the main limiting resource (Goldford et al, 2018). In these artificial communities, as in our functional tests, Enterobacteriaceae tend to grow better on sugars, and Pseudomonadaceae in organic acids (Estrela et al, 2020). An extreme case of this potential specialization was the Rosenbergiella species, which are known nectar inhabitants.…”
Section: Functional Characterization Of Bacteria Of the Ray Petal Csupporting
confidence: 69%
“…Results of the carbon use assay indicate that most of the cultured strains differentiated along a sugar-organic acid axis, corroborating known familial proclivities (Estrela et al, 2020), with most Enterobacteriaceae specializing on sugars and most Pseudomonadaceae specializing on organic acids ( Figure A4A).…”
Section: Functional Characterization Of Bacteria Of the Ray Petal Csupporting
confidence: 69%
“…Differences between the behavior of strains in pairwise versus complex communities point at higher-order ecological interactions that emerge in the community context. As previously shown in other studies, the underlying mechanisms may involve metabolic flexibility or mixed substrate utilization of the strains in the presence of competitors (41), metabolite cross-feeding and lack of waste-product inhibition and overall change in pH (11) or an excess of provided substrates in the medium.…”
Section: Discussionmentioning
confidence: 89%
“…Enrichment communities are an ideal system to test this hypothesis. In recent work, we have reported that increasing the number of supplied resources from 1 to 2 or 3 had a very small effect in the total biodiversity and did not lead to an appreciable increase in species richness (Estrela et al, 2020a; Figure 2). Consumerresource models with cross-feeding recapitulated this observation, and found that the identity of the nutrients in mixed-nutrient environments (i.e., whether they were two sugars or one sugar and one organic acid) had a larger effect on biodiversity than the number of those nutrients one adds.…”
Section: Understanding the Factors That Control The Diversity Of Microbial Communitiesmentioning
confidence: 84%